Disaster Management Implementation Analysis in the Working Area of Lubuk Buaya Community Health Center Padang City in 2023 - Rahmadani, Zaria; Gusrianti, Gusrianti; Yuliza, Wilda Tri (Alifah Health Science Symposium Proceeding, 2023)
Disasters are highly detrimental events for both communities and their surrounding environments, thus necessitating the presence of disaster management to mitigate the impacts of such events. The objective of this research is to comprehensively and objectively understand the implementation of disaster management in the operational area of Lubuk Buaya Community Health Center, Padang City. The qualitative descriptive research method was employed by conducting in-depth interviews with 9 informants. This study was carried out from March to August 2023 at the Lubuk Buaya Community Health Center, utilizing research instruments such as interview guidelines, observation sheets, document analysis, and checklist tables. The data obtained from this research is analyzed using technique triangulation and source triangulation. The research findings indicate that the executing personnel, facilities and infrastructure, funding, policies, and processes within disaster management, covering pre-disaster, during-disaster, and post-disaster phases, are in accordance with the applicable regulations. However, an obstacle was identified concerning the absence of a Disaster Management Unit (DMU) and standardized operating procedures (SOPs), despite being aligned with the regulations. The implementation of disaster management can effectively mitigate the impact of a disaster occurring within the operational area of Lubuk Buaya Community Health Center. It is expected that Lubuk Buaya Community Health Center will establish a Disaster Management Unit, develop SOPs, and conduct disaster response training for all healthcare personnel.